An FPGA Accelerator of the Wavefront Algorithm for Genomics Pairwise Alignment - Haghi, Abbas; Marco-Sola, Santiago; Alvarez, Lluc; Diamantopoulos, Dionysios; Hagleitner, Christoph; Moreto, Miquel (International Conference on Field-programmable Logic and Applications, 2021)
In the last years, advances in next-generation sequencing technologies have enabled the proliferation of genomic applications that guide personalized medicine. These applications have an enormous computational cost due to the large amount of genomic data they process. The first step in many of these applications consists in aligning reads against a reference genome. Very recently, the wavefront alignment algorithm has been introduced, significantly reducing the execution time of the read alignment process. This paper presents the first FPGA-based hardware/software co-designed accelerator of such relevant algorithm. Compared to the reference WFA CPU-only implementation, the proposed FPGA accelerator achieves performance speedups of up to 13.5 × while consuming up to 14.6 × less energy.